Enhancing renewable energy productivity and energy efficiency of energy projects: How does cost of capital influence? - Xiaojuan Yang; Huamin Zhou; Junjun Gao (Energy Strategy Reviews)
The study aims to test the renewable energy productivity and energy efficiency for energy projects with the role of cost of capital in China from 2009 to 2023. The study examined the results with correlation analysis, co-integration analysis, efficiency analysis, and generalized methods of moments (GMM) analysis technique. The results shown that the cost of capital for energy projects significantly determines renewable energy productivity. In addition, energy productivity also ensures the energy efficiency of renewable energy projects in China. The findings further explain that renewable energy productivity and efficiency foster energy transition significantly; it is also based on the cost of capital of the renewable energy project. In comparison, gross domestic product and urbanization show divergent controlling behavior in study results. Correspondingly, the study also suggested numerous policy implications for decision-makers. However, the novelty of research is contained in its framework. This investigation offers the first attempt at demonstrating how capital costs are detrimental to two other features typically studied separately – renewable energy productivity and energy efficiency.